Responsibility, perceived violence and prosociality in adolescents needing compensatory attention - Lamoneda-Prieto , J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
This work analyses, in a public educational centre associated to a Compensatory Education Programme how gender, the academic year and educational needs of educational support (SNES) influence responsibility in physical education, school violence and prosociality. 120 students took part in the project, age of 14.40 years (SD = 1.67), 62 out of them had been diagnosed with some SNES (51.7%) and 58 did not require any special support (48.3%). Results showed only differences among students who needed different educational attention in personal responsibility in physical education. Both gender and the academic year showed influential variables in social responsibility in physical education and prosociality. No differences were found in perceived school violence for the analised variables. Based on the data collected, practical considerations are provided for educational intervention with students at risk of social exclusion.